PHYSICAL AND MICROBIOLOGICAL PERFOMANCES OF ACIDIFIED FISH MEAL MADE BY DIPPING INTO EXTRACT SOLUTION OF SAUERKRAUT - Sulistiyanto, B.; Nugroho, K. (Diponegoro University, 2009)
An experiment was conducted to examine the influence of soaking time into extract solution ofSauerkraut on physic and microbial performances of acidified fish meal. Sauerkraut extract (LPS'ssollution) was made by fermentation of wastes vegetable market for 6 days. The LPS-extract was used toacidify